2011
DOI: 10.1080/17441692.2010.533686
|View full text |Cite
|
Sign up to set email alerts
|

Son preference and sterilisation use among young married women in two slums in Bengaluru city, India

Abstract: This paper explores the ways in which women’s sterilisation decisions are influenced by the combination of a preference for male children and a desire for smaller family size among young married women in two urban slums in Bengaluru, India. While both son preference and an emphasis on sterilisation are well-known demographic characteristics of most south-Asian countries, relatively little research has been conducted that links the two. We take advantage of a longitudinal survey of 416 unsterilised married wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…However the rural girls had difficulty in assessing higher education as colleges were far away. Jeffrey Edmeades 8 and co-workers who conducted a study in slums of Bangalore also reported sterilization choice was influenced by son preference. Bhasin 9 in his study has shown the number of sterilization as per birth order and percentage of Female children.…”
Section: Discussionmentioning
confidence: 99%
“…However the rural girls had difficulty in assessing higher education as colleges were far away. Jeffrey Edmeades 8 and co-workers who conducted a study in slums of Bangalore also reported sterilization choice was influenced by son preference. Bhasin 9 in his study has shown the number of sterilization as per birth order and percentage of Female children.…”
Section: Discussionmentioning
confidence: 99%
“…15 The studies from the different parts of India show a difference in the pattern of gender preferences. In a study from Bangalore, in Karnataka 16 , 62.2% of the urban women wanted at least one son. In a study from Howrah, in West Bengal 17 , 22.2% women had a son preference, while 37.8% and 36.2% had a balanced preference and no gender preference respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Gender preference varies from place to place and from society to society. Male preference is influenced by economic, religious, cultural, social, and emotional desires 3,4…”
Section: Introductionmentioning
confidence: 99%